Methodological approach to economic analysis and control of enterprises under conditions of economic systems transformation - Viknianska, A; Kharynovych-Yavorska, D; Sahaidak, M; Zhavoronok, A; Filippov, V (My University, 2021)
Purpose. To substantiate the methodological approach to the development of research components of the integrated system of complex economic analysis and internal control of the enterprise. Methodology. The main methods of this research are statistical methods, the latter being used for processing of statistic data; methods of formalization and mathematical simulation used for development of conceptual analysis base to control the enterprise’s activity. Findings. A complex model of diagnostics of enterprises’ activity in a competitive environment is proposed, which is based on the methodology of complex economic analysis with the use of financial and non-financial indicators. To assess the competitive advantages of the enterprise, we offer an algorithm to calculate an integrated indicator of the level of its competitiveness using a balanced scoring system. Originality. In the course of research, the scientific and methodological approach to a complex evaluation of influence of a research component on development of competitive strategy of the enterprise was developed. Unlike the existing ones, this approach involves: - development of an integrated system of complex economic analysis and internal control over business processes of enterprises with the use of modern information technologies, which allows assessing their competitiveness, forming a development strategy; - methodical procedures of internal control of the enterprise with the use of financial and operational budgets and management reports based on a balanced scoring system, using CVP-analysis, which allows forming flexible budgets. Practical value. The results of the study can be used by practitioners, scientists, government officials to monitor the development of the corporate architecture, to study enterprise development processes.
Keywords: competitive environment, complex economic analysis, internal control, balanced scoring system.